Fake News: What Is It, How Is It Made and Why It Works? - Forster, Renê (2021)
This work presents a review about information disorder, amidst which we include the so-called “fake news” phenomenon. Due to its increased potential for propagation in digital age, false or malicious content has impacted political and social life and its consequences range from rejection of health recommendations to violent disorders. In this review, we first define information disorder, considering some theoretical distinctions between its different manifestations. We then address the processes of production and dissemination of false and malicious content, focusing the producers and also the channels thought which such materials are spread. Next, we discuss reception of false content, reviewing works on the psychological and cognitive bases of gullibility.